BENCHMARKING ANALYSIS; IMPLEMENTATION OF BLOCKCHAIN SYSTEM IN SUPPLY CHAIN MANAGEMENT OF VEHGRO B.V - Dewi Claudia Agustin; Rob Berkhof (Diponegoro Journal of Accounting, 2022)
When adapted to logistics, technology of blockchain has the potential to significantly increase visibility all the way through global supply chains. As a consequence, it can improve goods tracking and provide data that cannot be altered to build trust among parties. Blockchain also ensures data security and transparency. This would contribute to the increasing demand for traceability in the food sector, as traceability has become a critical aspect in the field of food production as it ensures the quality and safety of the food product. The aims of this research is to analyze blockchain implementation and determine the implication of implementing a blockchain system in supply chain management, as well as to encourage VehGro to utilize blockchain in its supply chain in order to compete with its competition using benchmarking analysis. The study's investigation included both interviews and literature. The findings suggest that VehGro should implement private blockchain since it delivers various benefits to the organization. However, there are a few things that must be considered before implementing it.